Less is better than more with resection of periacetabular tumors – A retrospective 16 years study and literature review - Atzmon, Ran; Drexler, Michael; Dolkart, Oleg; Goldstein, Yariv; Dubin, Jeremy; Sternheim, Amir; Gortzak, Yair; Bickels, Jacob (Frontiers in Surgery, 2022)
Introduction: The intraoperative demands of a periacetabular tumor present a complicated situation for the surgeon and patient alike. Wide resections of periacetabular tumors create a sizeable bony defect that inevitably results in severe loss of function. Reconstruction of such defects usually requires using large metal implants, which results in surgical extension and complications, such as deep vein thrombosis and hip dislocation. This retrospective study aims to report patient outcomes after resection with no reconstruction of the bony defect as a salvage procedure for patients with low life expectancy. Methods: Records were reviewed of 16 consecutive patients diagnosed with malignant periacetabular tumors and underwent en-bloc resection without reconstructing their remaining bony defect. Measurements included: the duration of surgery, blood loss, hemoglobin levels and the need for blood transfusions, data on other hospitalization characteristics, and intraoperative and postoperative complications. Results: Sixteen patients with malignant periacetabular bone tumor and extensive bone destruction underwent wide periacetabular tumor resection with a mean follow-up of 75 months, and a mean age of 53 years. The average HOOS score was 46 (range: 20 to 76), and the mean MSTS score was 13% (range: 0 to 15). The mean operative time was 4.1 hours, and the mean blood loss was 1200 ml. At their most recent follow-up, the study patients had a mean leg length discrepancy (LLD) of 4.8 cm. The rate of postoperative complications was 37% and included iatrogenic urinary bladder injury, deep infection, and DVT. The survival rate for the limb with amputation as the endpoint was 88.9%. Conclusion: Wide resection of periacetabular tumors without reconstruction provides acceptable levels of function and was associated with shorter surgical time, less blood loss and fewer postoperative complications compared to resection with reconstruction. In addition, given the low life expectancy, the burden of a hospital stay and minimized postoperative complications compared with reconstruction. Therefore, this approach may be considered a viable surgical option in patients with an extensive malignant periacetabular tumor in a salvage surgery situation.